Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3847/1538-4357/ac9b00
|View full text |Cite
|
Sign up to set email alerts
|

On the Possibility of Generalized Wormhole Formation in the Galactic Halo Due to Dark Matter Using the Observational Data within the Matter Coupling Gravity Formalism

Abstract: In this article, we find the possibility of generalized wormhole formation in the galactic halo due to dark matter using observational data within the matter coupling gravity formalism. Keeping this as a target, we specifically employ f(R, T) gravity with (i) a variational approach concerning the metric, and (ii) the anisotropic source of matter. To understand the features of the wormholes, we thoroughly calculated and analyzed the energy conditions under f(R, T) gravity. We discuss the second embedded wormhol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 94 publications
0
8
0
Order By: Relevance
“…To conclude, this work validates the conformal symmetric wormhole solutions in ( ) f ,   gravity under noncommutative geometry. The authors [78] have identified the possibility of a generalized wormhole formation in the galactic halo due to dark matter using observational data within the matter coupling gravity formalism. In the near future, we plan to investigate various wormhole scenarios in alternative theories of gravity, as discussed in references [79-82].…”
Section: Results and Concluding Remarksmentioning
confidence: 99%
“…To conclude, this work validates the conformal symmetric wormhole solutions in ( ) f ,   gravity under noncommutative geometry. The authors [78] have identified the possibility of a generalized wormhole formation in the galactic halo due to dark matter using observational data within the matter coupling gravity formalism. In the near future, we plan to investigate various wormhole scenarios in alternative theories of gravity, as discussed in references [79-82].…”
Section: Results and Concluding Remarksmentioning
confidence: 99%
“…By taking the fundamental principle of general relativity (v tot < 1 for massive particles) and equations (17,18) into account, we arrive at…”
Section: Generalized Ellis-bronnikov Wormholementioning
confidence: 99%
“…Recently, an interest to the study of the GEB WHs has been increased in several contexts: to find a new class of solutions [17], to study the possibility of their formation in the galactic halo [18] and their quantum traversability [19].…”
Section: Introductionmentioning
confidence: 99%
“…This part will examine the embedding surface diagrams and extract the essential criteria for representing the embedded wormhole configurations. The visualized insights of the wormhole are separated by geometric embeddings [50,51]. We consider an equatorial slice 2 q = p since our metric is spherically symmetric (3), and the time coordinates t=constant value is fixed.…”
Section: Embedding Diagrammentioning
confidence: 99%